An evidence-based review of neuromodulation for the treatment and management of refractory angina. Issue 3 (September 2020) - Urits, Ivan; Patel, Anjana; Leider, Joseph; Anya, Anthony; Franscioni, Henry; Jung, Jai Won; Kassem, Hisham; Kaye, Alan D.; Viswanath, Omar
Abstract : Angina pectoris is defined as substernal chest pain that is typically exacerbated by exertion, stress, or other exposures. There are various methods of treatment for angina. Lifestyle modification and pharmacological management are considered as conservative treatments. If these medications do not result in the resolution of pain, more invasive approaches are an option, like coronary revascularization. Refractory angina (RA) is differentiated from acute or chronic angina based on the persistence of symptoms despite conventional therapies. Overall, the prevalence of RA is estimated to be 5%–15% in patients with coronary artery disease, which can account for up to 1, 500, 000 current cases and 100, 000 new cases in the United States per year. Spinal cord stimulation treatment is a viable option for patients who are suffering from RA pain and are either not candidates for revascularization surgery or are currently not being well managed on more traditional treatments. Many studies show a positive result.